Faktor Ibu dan Faktor Bayi Dengan Respon Fisiologi (Saturasi O2) Pada Bayi Prematur Yang Dilakukan Developmental Care - Gustop Amatiria; Armen Patria (Politeknik Kesehatan Tanjung Karang, 2017)
Prematurity is the leading cause of death in children under the age of 5 years in the world and in Indonesia in 2012 recorded around 675,700 or 15.5 per 100 births. Premature infant mortality is largely due to maladaptive environmental response extrauterine causing the baby's environmental stress causing problems in the circulation, oxygenation and metabolic that can interfere with the growth and development neurophysiologic of a baby so that in premature infants should be done Developmental Care Efforts (Light and Sound Setting). Differences Maternal and infant factors may affect the optimization of the application of developmental care by regulating light and sound received by infants in an effort to optimize the growth of infant development in the perinatology space to achieve a normal physiological response in which one indicator is the adequacy of O2 indicated by oxygen Saturation value (Sa O2). This study aimed to determine the relationship between mother and infant factors after Development Care (light and sound settings) received with physiological response (Sa O2), premature babies. The research design used was analytical with cross sectional approach. The samples used by 45 infants were selected by consecutive sampling technique. The analysis used a correlation test to determine the strength of the relationship (r) and 95% confidence intervals. The results showed that there was a significant relationship between economic status and SaO2 (r = -0.509; p value = 0.016), but no significant relationship between maternal age and SaO2 (r = -0.005; p-value = 0.982); history of diseases during pregnancy with SaO2 (r = 0.121; p-value = 0,591); gestational age with SaO2 (r = -0.004; p-value = 0.985); neuromuscular maturity with SaO2 (r = -0.64; p-value = 0.777); weight with SaO2 (r = -0.189; p-value = 0.399); length of body with SaO2 (r = -0.028; p-value = 0.901). Keywords: Mother, Premature infant, Developmental care